An Overview of Artificial Immune System Algorithms for Industrial Monitoring ISSN 1974-6059 Cd-Rom ISSN: 1974-6067 - A. Abdelhadi; Mouss Leila Hayet (IRECOS International Review on Computers and Software, 2011)
We describe in this paper an overview of artificial immune system algorithms to solve the classification problem in industrial monitoring. We present artificial immune system algorithms, starting with the negative selection that happens to be a rich source of inspiration. We also, detail the clonal selection algorithm, which is based on the clonal selection theory. Finally, we detail other algorithms based of agent including the immune system and dendritic cell algorithm. In the end, we summarize the differences and similarities of the works discussed and we conclude on the prospects related to the approach of the algorithms of artificial immune systems for industrial monitoring to solve the classification problem. Copyright © 2011 Praise Worthy Prize S.r.l. - All rights reserved